THE INFLUENCE OF WORK RECOGNITION, WORK MOTIVATION, AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF EMPLOYEE ENGAGEMENT AMONG INDONESIAN DISTRICT COURT JUDGES - Anang Riyan Ramadianto; Sri Wartini; Euis Soliha; Sandy Arief (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Grounded in Self-Determination Theory (SDT) and Friedman’s Legal System Theory, this study examines the effects of work recognition (WR), work motivation (WM), and career development (CD) on employee performance (EP) with employee engagement (EE) as a mediating variable among judges in Indonesian District Courts. A quantitative approach was employed using questionnaires distributed to 151 judges across Indonesia, and the data were analyzed using PLS-SEM with SmartPLS 4.0. The findings revealed that work motivation and career development positively and significantly affect employee performance, whereas work recognition does not directly influence employee performance. However, work recognition, work motivation, and career development significantly influence employee engagement, while employee engagement positively affects employee performance. Furthermore, employee engagement significantly mediates the relationships between work recognition, work motivation, career development, and employee performance. These findings indicate that organizational support, motivation, and professional development are essential in strengthening judges’ engagement, professionalism, and performance within judicial institutions.